1986
DOI: 10.1007/bf00179197
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxydopamine lesions of the nucleus accumbens, but not of the caudate nucleus, attenuate enhanced responding with reward-related stimuli produced by intra-accumbens d-amphetamine

Abstract: Intra-accumbens d-amphetamine enhances responding for reward-related stimuli (conditioned reinforcers, CRs), whereas intra-caudate d-amphetamine has only weak and variable effects (Taylor and Robbins 1984). The present experiment further examined the involvement of the nucleus accumbens and the role of dopamine (DA) in this effect. Thirsty rats were trained to associate a flash of a light and movement of a dipper (CR) with water. After implantation of permanent guide cannulae aimed at the nucleus accumbens, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
139
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(153 citation statements)
references
References 27 publications
(38 reference statements)
14
139
0
Order By: Relevance
“…Damage to the hippocampal formation was very similar to that previously described [55]. Histological analyses revealed that all lesioned animals that received kainic acid/colchicine lesions had extensive bilateral damage to the hippocampal formation (see Fig.…”
Section: Histologysupporting
confidence: 82%
See 1 more Smart Citation
“…Damage to the hippocampal formation was very similar to that previously described [55]. Histological analyses revealed that all lesioned animals that received kainic acid/colchicine lesions had extensive bilateral damage to the hippocampal formation (see Fig.…”
Section: Histologysupporting
confidence: 82%
“…This enhancement in drug-induced activity following extensive hippocampal damage: (i) occurs as a direct function of increased locomotion and not indirectly, from reductions in competing behaviors [59]; (ii) is dependent on the integrity of the mesolimbic dopamine (DA) projection, as 6-OHDA lesions of the NACC block this effect [59]; (iii) occurs specifically in response to pharmacological stimulation of dopamine D2 receptors, which is consistent with the possibility of underlying receptorbased changes [38]; and (iv) corresponds to increases in amphetamine stimulated DA release in the NACC [60]. It is presumed that these changes occur as a function of the degeneration of hippocampal efferents innervating the NACC [4,17,19,20,27,50,51,55,56,63].…”
Section: Introductionmentioning
confidence: 89%
“…The discrepancy between the Crean et al study and our study may relate to the difference in sample size (n ¼ 20 in their study vs n ¼ 11 in our study) or the different dose: Crean et al administered 100 mg drinks, associated with an average 84% reduction of TRPÀ levels relative to baseline, while we administered 75 mg drinks, which reduced TRPÀ levels by 61% relative to baseline. Nevertheless, the differential sensitivity of the two measures observed here might be interesting in the context of their association with dissociable underlying corticostriatal circuitries (Taylor and Robbins, 1986;Jentsch and Taylor, 1999;Wyvell and Berridge, 2000;Eagle and Robbins, 2003a, b;Aron et al, 2003;Robbins, 2000).…”
Section: Discussionmentioning
confidence: 81%
“…The neurobiology of these distinct actions has been well elucidated for cocaine and amphetamine (Taylor and Robbins 1984;Taylor and Robbins 1986;Taylor and Horger 1999;Fletcher and Korth 1999;Fletcher et al 1999;See et al 2001). While basic circuits underlying nicotine reinforcement have been extensively investigated Corrigall et al 1994;Corrigall et al 1992;Corrigall and Coen 1991;Jose Lanca et al 2000;Lanca et al 2000), only limited research has been conducted on the neural underpinnings for the interactions between nicotine and nonpharmacological stimuli (Liu et al 2004;Cohen et al 2005;Paterson et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Infusions of damphetamine into NAcc but not the caudate putamen or thalamus dose-dependently potentiate responding for conditioned stimuli (Taylor and Robbins 1984). Dopaminergic signaling is important for this effect, as suggested by evidence that responding for conditioned reinforcers is accelerated by intra-NAcc dopamine infusions , and reduced by dopamine depletion of the NAcc (Taylor and Robbins 1986;Parkinson et al 2002). Conversely, serotonin depletion augments the potentiation of conditioned reinforcement induced by intra-NAcc amphetamine (Fletcher et al 1999) and in separate studies prior infusion of serotonin (5-HT) or prior activation of 5-HT 1B receptors in the NAcc attenuated the behavioral effects of intra-NAcc amphetamine (Fletcher and Korth 1999).…”
Section: The Neurobiology Of Nicotine Reinforcementmentioning
confidence: 99%